BEHAVIORAL MODELS OF REGULATING INFORMATION AND CYBERSECURITY IN PUBLIC AUTHORITIES IN DIGITAL TRANSFORMATION CONDITIONS - Petroie, Ivan (Public Management and Policy, 2026)
The subject of the study is behavioral models of regulating information and cybersecurity in public authorities in digital transformation conditions. The article aims to conduct a comparative analysis of leading behavioral models of information and cybersecurity and to develop recommendations for public authorities to improve behavioral information security based on them. The methodological foundation of the study includes the systemic and interdisciplinary approaches, structural and comparative analysis, synthesis, and modelling. The source base consists of scientific publications on the topic of the study indexed in Scopus, selected and verified using Scopus AI tools. The conceptual basis of the study is the taxonomy of unintentional, intentional, and malicious behavior in the system of information and cybersecurity, which allows one to consider the information and cyber space of public authorities as a complex systemic phenomenon encompassing the interaction of people, software, and networks. As a result of the study, three groups of behavioral models of information and cybersecurity are systematized: 1) traditional cognitive models; 2) multidimensional operational models; 3) risk management models. It is established that the quality of regulatory documents and policies of public authorities is a particularly important tool for ensuring compliance with information security requirements. The advisability of applying a comprehensive value‑oriented and multidimensional process‑oriented model of managing behavioral information security in public authorities in digital transformation conditions is substantiated.